Estudo da microestrutura da camada de cobrimento de concreto com altos teores de cinza volante - Silveira, Rodrigo Goettems da (2004)
The increase in the durability of the concrete structures causes greater useful life of the same ones, influencing directly in the improvement of the constructions and the quality of life of the inhabitants. So that a durable structure either is necessary that it is resistant to the aggressive agents who penetrate from the environment for the interior of the concrete, through the pores of the covering layer, being able to reach the reinforcement, causing the corrosion process. The reduction of the dimensions of the pores not only brings the increase in the resistance, but adjusted protection more for the steel for the biggest resistance to the fluid percolating. In the present research the main factors had been studied that influeces in the microstructure of the layer of covering of the concrete. In this study, had been evaluated the characteristics of the microstructure of the covering of concrete with 50% of fly ash (FA) in substitution to the cement for two water/cementitious materials (w/cm) relations, in three layers from the surface until a depth of 60 mm; and the compressive strength of the concrete in the ages of 28 and 91 days for three w/cm, comparing molded samples (MSs) cured in controlled conditions with archetypes extracted samples cured outdoors. Aiming at to restitute the reserve of calcium hydroxide of the concrete, in some admixtures was added lime in amount of 20%. In the tests of axial compressive strength it was verified that, in general, in the lower w/cm relations, the extracted samples had presented higher strength than the MSs. Tests of mercury intrusion porosimetry for the determination of the dimensions and distribution of the pores of the covering layer had been carried through. These tests had shown that the most superficial layer of the concrete presents more open porosity than the interior one. It was verified that, with the increase of the depth of study, the microstructure of concrete was denser. The bound water tests had demonstrated that in concrete with bigger relation w/cm, it increased the amount of hidration products with the increase of the studied depth. In admixtures with lower w/cm and without lime addition, this relation revealed inverse. The admixtures with lime addition had presented bound water amount higher in the layers most internal of the concrete. The tests of search electronic microscopy (SEM) had been used for the qualitative confirmation of the comments carried through in the porosity tests